Optimization and techno-economic comparison of regenerators and recuperators in sCO2 recompression Brayton cycles for concentrating solar power applications. (15th May 2022) - Reznicek, Evan P.; Neises, Ty; Braun, Robert J.
Abstract: Supercritical CO 2 power cycles might be capable of providing the cost reductions and efficiency improvements necessary to reach concentrating solar power (CSP) cost targets, but require large, highly effective recuperators. Fixed-bed regenerators are a periodic heat exchanger that could be an effective yet low-cost alternative to these recuperators. This study presents a techno-economic comparison of regenerators and recuperators for a 100 MWe supercritical CO 2 power cycle for CSP applications. We quantify the levelized cost of energy (LCOE) for the power plant with both types of heat exchangers, and explore sensitivity of LCOE to parameters such as CSP-specific capital costs, power cycle component capital costs, and regenerator valve replacements costs. Results indicate that the incumbent printed circuit heat exchangers achieve the lowest LCOE, unless the upper extreme of PCHE capital cost and lower extremes of regenerator and valve capital and O&M costs are realized. Sensitivity analysis also illustrates that the primary heat exchanger cost is the most influential of power cycle components, and that CSP component capital cost is more influential than power cycle capital costs. This illustrates the importance of reducing the cost of heliostats, receivers, and thermal energy storage for achieving CSP LCOE targets. Highlights: Techno-economic analysis uses vendor-data derived cost correlations from literature. Comparison of PCHEs and regenerators for recuperation. PCHEs enable lower LCOE than regenerators under most circumstances. CSP-specific components influence cost much more than power cycle components. Economic optimization recommends lower recompression fraction than prior studies.